Aus meinem Leben und Denken - Schweitzer, Albert 1875-1965; Grabs, Rudolf (Hamburg Meiner, 1980)
Albert Schweitzer provides information about his life and thoughts in simple and clear language. Growing up in Alsace, he first studied theology and philosophy in Strasbourg and attended lectures in music theory to complete his musical education. In 1904, he decided to go to Africa, not as a missionary, but as a doctor, in order ‘not only to live for science and art, but to dedicate himself to direct human service’. In addition to his work as a doctor in Lambarene, Schweitzer continued to devote himself to music and philosophy; he published Bach's organ works, went on concert tours and published his writings on cultural philosophy. (Translated with DeepL.com)
mit einem abschliessenden Kapitel "Die weiteren Jahre" (1931-1965) von Rudolf Grabs.
Keywords: Biography; Music philosophy and esthetics